2017
DOI: 10.1007/s12282-017-0764-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced amenorrhea and the resumption of menstruation in premenopausal women with hormone receptor-positive early breast cancer

Abstract: The incidence of CIA, the resumption of menstruation and duration of CIA after chemotherapy depend greatly on the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
2
16
1
Order By: Relevance
“…Regarding independent factors related to CIA, our study revealed only age older than 45 years-old impacted irreversible CIA. This result was similar to previous reports that showed younger ages related to the resumption of menstruation [6][7][8][9][10]. However, Meng et al [10] published their study about this issue in 73 premenopausal breast cancer women who received adjuvant chemotherapy for early-stage breast cancer (Stages I-III) and found that CIA significantly related to age at diagnosis and tamoxifen usage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding independent factors related to CIA, our study revealed only age older than 45 years-old impacted irreversible CIA. This result was similar to previous reports that showed younger ages related to the resumption of menstruation [6][7][8][9][10]. However, Meng et al [10] published their study about this issue in 73 premenopausal breast cancer women who received adjuvant chemotherapy for early-stage breast cancer (Stages I-III) and found that CIA significantly related to age at diagnosis and tamoxifen usage.…”
Section: Discussionsupporting
confidence: 89%
“…This prevalence rate was similar to a previous publication from Japan. Kota et al [7] studied menstruation in 101 premenopausal Stage I-III hormonal receptor-positive Japanese breast cancer women who received chemotherapy. The authors defined CIA as the disappearance of periodic menstruation during chemotherapy and if the menstruation appeared after finishing the course of chemotherapy, this state was defined as a resumption of menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, adjuvant chemotherapy has improved the disease-free survival and overall survival of breast cancer patients; however, the detrimental effects caused by chemotherapy remain unclear. 22 25 We specifically assessed the changes of serum lipids and apolipoproteins following the administration of chemotherapy in breast cancer patients. When the postoperative patients received chemotherapy, their levels of TC and LDL-C reduced after the first cycle because cancer drugs needed cholesterol depletion to cross the cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, amenorrhea was defined as the disappearance of the menstrual cycle during chemotherapy or postchemotherapy for 6 months; if the menstruation appeared periodically again within 1 year postchemotherapy, the state of the women was defined as “recovery of menstruation”. 27 The changes in menstruation postchemotherapy were followed-up.…”
Section: Patients Animals and Methodsmentioning
confidence: 99%